Exploring the psychological impact of working during COVID-19 on medical and nursing students: a qualitative study. Issue 6 (23rd June 2022) - Griffin, Louise; Riley, Ruth
Abstract : Objectives: To identify the psychological impact of working during the COVID-19 pandemic on medical and nursing students' psychological well-being. To inform recommendations for the provision of future student well-being support. Design: An interpretative qualitative, semistructured interview study employing maximum variation sampling, snowball sampling and a thematic analysis. Setting: A large West Midlands (UK) university with medical and nursing undergraduate and postgraduate programmes. Study undertaken between January and May 2020. Participants: A purposive sample of eight medical (six women and two men) and seven nursing (all women) students who worked >2 weeks in a healthcare setting during the COVID-19 pandemic (from 1 March 2020 onwards). Results: Four core themes with corresponding subthemes were identified: (1) COVID-19 sources of distress—working conditions, exposure to suffering, death and dying, relationships and teams, individual inexperience and student identity, (2) negative impact on mental health and well-being—psychological and emotional distress, delayed distress, exhaustion, mental ill health, (3) protective factors from distress—access to support, environment, preparation and induction, recognition and reward, time for breaks and rest and (4) positive experiences and meaningful outcomes. Conclusions: Student pandemic deployment has had a significant negative impact on students' psychological well-being, as a result of demanding working conditions, unprecedented exposure to death and suffering and lack of preparation for new job roles. Universities and healthcare organisations must formally acknowledge this impact and provide well-being support for distressed students working in such challenging contexts. They must also establish more supportive and inclusive healthcare environments for medical and nursing students in future pandemic and postpandemic circumstances, through the implementation of support systems and adequate preparation.